Rooting Gilbert's Multi-Modal Argumentation in Jung, and its Extension to Law - Novak, Marko (Informal Logic)

(untitled) (Informal Logic, 2020)
This paper discusses how an understanding of Jung's psychological types is important for the relevance of Gilbert's multi-modal argumentation theory. Moreover, it highlights how the types have been confirmed by contemporary neuroscience and cognitive psychology. Based on Gilbert's approach, I extend multi-modal argumentation to the area of legal argumentation. It seems that when we leave behind the traditional fortress of “logical” legal argumentation, we "discover" alternate modes (such as the intuitive, emotional, and sensory) that have always been present, concealed in the theoretically underestimated rhetorical skills of arguers.